THE CHANGING ROLE OF RETAILING THEORY IN AN EXMERGING ECONOMY - Dr Ojo Monday Isiramen; Dr Omoruyi B. Elaho (Scholar Express Journals, 2021)
The evolution of retailing has elicited interest from academics across a range of disciplines including economics, history, geography, and marketing. Due to its interdisciplinary appeal, the corpus of knowledge on retailing is composed of many disparate variables of analysis - from transaction costs, and entrepreneurs, to environmental factors, and the dispersion of stores. This paper studies retailing theories. The study identified three main streams of thought explaining retailing evolution: environmental theory, cyclical theory and conflict theory. These theories have been developed to explain the patterns and trends that manifest in retailing and selling. Cyclic theories hypothesize the retail environment and competitive practices of retailers follow a slightly, repeating pattern, with clear identifiable stages. The cyclical models assume that retailers pass through before-known stages and follow a certain cycle. Well-known theories within the cyclical theory are the wheel of retailing, the retail accordion and the concept of the Big Middle. On the other hand, noncyclic theory patterns present the retail environment at one in which there are different forces, that constant adaptation without the presence of repeating pattern. These retailing theories have received criticisms on the premise that they were postulated in the context of American culture and economic system. Contrastly, it is vital for retailers to fully understand major theories of retailing and to act accordingly. This suggests that these theories can be perceived in successful retailing, which often reflects change and staying up-to-date
Keywords: selling; postulated; criticisms; adaptation